2016
DOI: 10.1136/jramc-2016-000635
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of exercise related leg pain in young soldiers; a review of the literature and current practice in the Dutch Armed Forces

Abstract: Overuse injuries of the leg are a common problem for young soldiers. This article reviews the literature concerning the prevention and treatment of exercise related leg pain in military settings and presents the latest developments in proposed mechanisms and treatments. Current practice and treatment protocols from the Dutch Armed Forces are reviewed, with an emphasis on the most prevalent conditions of medial tibial stress syndrome and chronic exertional compartment syndrome. The conclusion is that exercise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 113 publications
0
44
1
3
Order By: Relevance
“…It is of note that no athlete was clinically suspected of having a tibial stress fracture, one of the more important differential diagnoses when assessing overuse injuries along the medial aspects of the tibia. However, tibial stress fractures are extremely rare in The Netherlands, even in the Dutch Royal Army 30. We acknowledge that in other geographical areas (eg, Australia,31 Great Britain,32 Israel33 and the USA34) the prevalence of tibial stress fractures seems much higher, and, possibly this may affect the ease to distinguish between MTSS and tibial stress fracture.…”
Section: Discussionmentioning
confidence: 95%
“…It is of note that no athlete was clinically suspected of having a tibial stress fracture, one of the more important differential diagnoses when assessing overuse injuries along the medial aspects of the tibia. However, tibial stress fractures are extremely rare in The Netherlands, even in the Dutch Royal Army 30. We acknowledge that in other geographical areas (eg, Australia,31 Great Britain,32 Israel33 and the USA34) the prevalence of tibial stress fractures seems much higher, and, possibly this may affect the ease to distinguish between MTSS and tibial stress fracture.…”
Section: Discussionmentioning
confidence: 95%
“…In the Dutch Armed forces, as in the British and American forces, ERLP is a major cause of decreased readiness to continue with training. [1] Continued effort is warranted in both the primary prevention and treatment of these injuries. In previous studies, positive results were reported with gait retraining in the treatment of soldiers diagnosed with CECS.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Surgical intervention entails opening of the enveloping fascia via a fasciotomy using an open, a minimally invasive, or an endoscopic technique. [12][13][14] Traditionally, management of CECS starts with conservative measures, followed by surgical intervention in case of treatment failure or severely disabling symptoms. 11 This sequence is merely based on clinical experience; a surgery first approach, or a combination of surgery and conservative measures, might also be beneficial.…”
mentioning
confidence: 99%